Analysis of modern innovative approaches to the provision of construction projects - Arutiunian, I.; Arutiunian, Y; Kolisnyk, V.; Halushko, D.; Zubkov, S. (Ways to Improve Construction Efficiency, 2024)
The scientific article reveals the role of logistics in construction, its impact on the efficiency of projects and modern methods and technologies that contribute to the optimization of logistics processes. Promising trends in the provision of construction objects using the field of knowledge logistics are studied. The relevance of the problems of the modern construction industry, which faces a number of challenges that require effective management of the flow of materials, equipment, information and human resources from suppliers to construction sites, is indicated. Studies indicate that optimizing logistics processes can reduce costs, increase productivity, and improve the level of completion of construction projects. The prospects and possibilities of using the field of knowledge logistics as a modern operating tool for the provision of construction projects are substantiated. This is especially important in the face of rapid technological changes and volatile market conditions. As a result of the analysis, opportunities for the introduction of innovative technologies and methods in the construction industry have been identified. The integration of advanced solutions allows us to improve the processes of ensuring construction at all stages. Based on the results of our research, the basic principles of the use of logistics in construction are determined, which contribute to improving the efficiency of logistics processes and ensuring the successful implementation of construction projects. The proposed approach to the application of the principles of logistics in construction contributes to the harmonization of the processes of ensuring construction. It allows you to thoroughly analyze all aspects of logistics processes, including inventory management, coordination with suppliers and manufacturers, demand forecasting and the use of modern technologies., ensuring the timely delivery of materials, optimal use of resources and improving the efficiency of the project as a whole.